Choice of comparator in restorative trials: A network analysis. Issue 12 (December 2015) - Schwendicke, Falk; Blunck, Uwe; Paris, Sebastian; Göstemeyer, Gerd
Highlights: Comparator choice in restorative trials is assessed via network analysis. Comparisons against certain established standards are common. Many trials compare within, not between material classes. It remains unclear if such network geometry indicates a biased research agenda. Abstract: Objectives: The choice of trial comparators might impact on the validity of the available evidence. We aimed at evaluating dental restorative trial networks and the underlying comparisons made, hypothesizing that certain comparators are disproportionally preferred or avoided. Methods: A systematic review was performed via Medline, CENTRAL and EMBASE. Randomized controlled trials on dental restoration or adhesive materials published 2005–2015 were included. Social network analysis techniques were used to assess trial networks. Results: 114 studies on 15 321 restorations placed in 5232 patients were included. 57 and 53 trials investigated restoration of cervical and load-bearing cavities, respectively. Four trials on non-cervical, non-load-bearing cavities did not form a network and were not evaluated. The most frequently assessed material combination was hybrid composites placed using 2-step etch-and-rinse adhesives. In cervical cavities, the majority of trials compared adhesives, not restorative materials. In load-bearing cavities, testing other restorative materials (ormocers, compomers) was common, too. In both networks, comparisons within material classes were frequent. There was significant homophily ( p  < 0.001), i.e. certain material classes were preferred as comparators, while this preference seemed to change with time. Only very few comparisons yielded significant differences between materials. Significance: The disproportional use of certain material classes as comparator might be due to their perceived role as gold standard. Compared with other scientific disciplines, dental restorative trial networks seem less prone for bias by comparator choice. Factors underlying the network geometry should be assessed to understand drivers of the research agenda.